On the Challenges and Opportunities of Physically Situated Dialog - Bohus, Dan; Horvitz, Eric (2010)
We outline several challenges and opportunities for building physically situated systems that can interact in open, dynamic, and relatively unconstrained environments. We review a platform and recent progress on developing computational methods for situated, multiparty, open-world dialog, and highlight the value of representations of the physical surroundings and of harnessing the broader situational context when managing communicative processes such as engagement, turn-taking, language understanding, and dialog management. Finally, we outline an open-world learning challenge that spans these different levels.